Postprocessing synchronization of a laser scanning system aboard a UAV - Machado, Marcela Do Valle [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP]; Torres, Fernanda Magri [UNESP]; Campos, Mariana Batista [UNESP] (American Society for Photogrammetry and Remote Sensing, 2019)
Synchronization of airborne laser scanning devices is a critical process that directly affects data accuracy. This process can be more challenging with low-cost airborne laser scanning (ALS) systems because some device connections from off-the-shelf sensors are less stable. An alternative to synchronization is performing a postprocessing clock correction. This article presents a technique for postprocessing synchronization (off-line) that estimates clock differences based on the correlation between the signals from the global navigation satellite system (GNSS) trajectory and the light detection and ranging (lidar) range, followed by refinement with a least-squares method. The correlation between signals was automatically estimated considering the planned flight maneuvers, in a flat terrain, to produce altimetric trajectory variations. Experiments were performed with an Ibeo LUX laser unit integrated with a No-vAtel SPAN-IGM-S1 inertial navigation system that was transported by an unmanned aerial vehicle (UAV). The planimetric and altimetric accuracies of the point cloud obtained with the proposed postprocessing synchronization technique were 28 cm and 10 cm, respectively, at a flight height of 35 m.